The Effect of Azolla microphylla Biomass on the Abundance of Zooplankton in the Maintenance Media of Catfish (Pangasianodon hypophthalmus) - Nurul Hidayat; Syafriadiman Syafriadiman; Saberina Hasibuan (Jurusan Budidaya Perairan, Fakultas Perikanan dan Kelautan, Universitas Riau, 2022)
Azolla microphylla on the surface of the water media can function as a phytoremediation that is able to improve water quality factors and provide nutrients in the waters so as to increase the abundance of zooplankton in the rearing media. This research was carried out in August-September 2021 at the Experimental Pond and Laboratory of Fish Parasites and Diseases, Faculty of Fisheries and Marine, Riau University. This study aims to determine the effect of Azolla microphylla biomass and to obtain the best biomass to increase the abundance of zooplankton in Siamese catfish (Pangasianodon hypophthalmus) rearing media using peat water. This study used a completely randomized design (CRD) 1 factor with 4 treatment levels and 3 replications. The treatments in this study were Azolla microphylla with different biomass, namely AM0 (Control), AM1 (20 g m-2), AM2 (40 g m-2) and AM3 (60 g m-2). The results showed that the best treatment was AM3 treatment (60 g m-2) which produced an average zooplankton abundance of 1503 ind/L and was able to support the life of Siamese catfish (P. hypophthalmus) for 28 days of rearing by producing absolute weight growth ( 2.41 g/head). During the study, 4 species of zooplankton were found from the Protozoa and Rotifera classes. The Protozoa class consists of 1 species, namely Pleodarina sp., while from the Rotifera class there are 3 species, namely Brachionus bidentata, Monostyla sp. and Philodina roseola.